Human Embryonic Stem Cells Acquire Responsiveness to TRAIL upon Exposure to Cisplatin - Lucie Pešková; Vladimír Vinarský; Tomáš Bárta; Aleš Hampl (Hindawi Limited, 2019)
Tumor necrosis factor-related apoptosis-inducing ligand-TRAIL-is a protein operating as a ligand capable of inducing apoptosis particularly in cancerously transformed cells, while normal healthy cells are typically nonresponsive. We have previously demonstrated that pluripotent human embryonic stem cells (hESC) are also refractory to TRAIL, even though they express all canonical components of the death receptor-induced apoptosis pathway. In this study, we have examined a capacity of DNA damage to provoke sensitivity of hESC to TRAIL. The extent of DNA damage, behavior of molecules involved in apoptosis, and response of hESC to TRAIL were investigated. The exposure of hESC to 1 μM and 2 μM concentrations of cisplatin have led to the formation of 53BP1 and γH2AX foci, indicating the presence of double-strand breaks in DNA, without affecting the expression of proteins contributing to mitochondrial membrane integrity. Interestingly, cisplatin upregulated critical components of the extrinsic apoptotic pathway-initiator caspase 8, effector caspase 3, and the cell death receptors. The observed increase of expression of the extrinsic apoptotic pathway components was sufficient to sensitize hESC to TRAIL-induced apoptosis; immense cell dying accompanied by enhanced PARP cleavage, processing of caspase 8, and full activation of caspase 3 were all observed after the treatment combining cisplatin and TRAIL. Finally, we have demonstrated the central role of caspase 8 in this process, since its downregulation abrogated the sensitizing effect of cisplatin.